Peran Self-Efficacy terhadap Kemampuan Representasi Matematis Siswa: Tinjauan Literatur - Nopalia Susanti (Jurnal Wahana Literasi Pendidikan, 2026)
This study aims to review the role of self-efficacy in students' mathematical representation abilities. Mathematical representation ability is important in mathematics learning because it helps students express ideas in visual, symbolic, and verbal forms. The research employed a Systematic Literature Review (SLR) method on scientific articles published between 2020 and 2025, which were retrieved through Google Scholar with the assistance of Publish or Perish. The articles were selected based on topic relevance, methodological clarity, their connection to self-efficacy, and discussions related to mathematical representation abilities. The findings indicate that students with high self-efficacy tend to demonstrate more comprehensive and flexible mathematical representations. In contrast, students with low self-efficacy often encounter difficulties in selecting appropriate forms of representation and communicating mathematical ideas. The review also reveals that active, collaborative, and problem-based learning strategies can support the enhancement of both self-efficacy and students' mathematical representation abilities. Therefore, self-efficacy should be considered an important psychological factor contributing to success in mathematics learning.